Factors Affecting Adherence To Consumption Of Fe Tablets In The Prevention Of Anemia In High School Students: A Literature Review - Rahayu, Sri; Said, Mohamed Saifulaman Mohamed; Sansuwito, Tukimin Bin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: Anemia is when the blood's hemoglobin (Hb) level is less than usual. Anemia is a nutritional problem that is prevalent throughout the world. Anemia occurs not only in developing countries but also in developed countries. Anemia can occur anywhere and can happen to anyone. The impact of anemia on adolescent girls in the short term is to disrupt growth and development, reduce physical ability and work activity, reduce learning concentration, and hurt the digestive tract, central nervous system, cardiovascular system, and immunity. Material and Methods: This research is a literature review. Articles according to the theme were selected from 2018-2023 from electronic databases such as Science Direct, PubMed, and Google Scholar. We used the PRISMA method for the analysis of the literature review. Results: From 217 selected articles, 16 eligible studies were thoroughly reviewed, and only 10 could be analyzed. The results of the ten articles examined that many factors affect adherence to taking Fe tablets, namely knowledge that dominates in the matter. Conclusion: With the help of their parents, families, and teachers, the students exhibited a promising level of compliance with taking iron tablets, which is anticipated to lower the prevalence of anemia among teenage girls.